Sex Differences in Spatiotemporal Consistency and Effective Connectivity of the Precuneus in Autism Spectrum Disorder. - Gao, Le; Zhang, Tengda; Zhang, Yigeng; Liu, Junfeng; Guo, Xiaonan (Journal of Autism & Developmental Disorders, 2026)
Autism spectrum disorder (ASD) has been reported to exhibit altered local functional consistency. However, previous studies mainly focused on male samples and explored the temporal consistency in the ASD brain ignoring the spatial consistency. In this study, FOur-dimensional Consistency of local neural Activities (FOCA) analysis was used to investigate the sex differences of local spatiotemporal consistency of spontaneous brain activity in ASD. This study used resting-state functional magnetic resonance imaging data from the Autism Brain Imaging Data Exchange database, including 64 males/64 females with ASD and 64 male/64 female neurotypical controls (NCs). Two-way analysis of variance was performed to ascertain diagnosis-by-sex interaction effects on whole brain FOCA maps. Moreover, granger causal analysis was used to investigate effective connectivity between the brain regions with interaction effects and the whole-brain in ASD. Significant diagnosis-by-sex interaction effects on FOCA were observed in the bilateral precuneus (PCUN), bilateral medial prefrontal cortex and right dorsolateral superior frontal gyrus. Specifically, FOCA was significantly increased in males with ASD but decreased in females with ASD in the PCUN compared with the sex-matched NC group. In addition, the lack of sex differences in the causal influences from the bilateral anterior cingulate cortex/medial prefrontal cortex to the PCUN was observed in ASD. Our results reveal altered sex differences in the spatiotemporal consistency of spontaneous brain activity and functional interaction of the anterior and posterior default mode network (DMN) in ASD, highlighting the critical role of the DMN in the sex heterogeneity of ASD.